SILENCE AS THE RHETORIC OF RESISTANCE IN HEISNAM KANHAILAL’S THEATRE PRACTICE - Mandal, Pranab Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The theatre practice of Heisnam Kanhailal and his cocreator of performance, Heisnam Sabitri is less of words, speeches and dialogues than found in conventional proscenium theatre. Both Kanhailal and Sabitri believe that theatre has a language of its own and that language is not necessarily a language of verbal communication. In their theatre, action is expressed more through body movements, physical gestures and sounds than through spoken words as they believe that non-verbal silent communication of a theatrical action or feeling is more powerful than the spoken ones. This unusual mode of theatrical narrative has helped Kanhailal to form a rhetoric of resistance against various forms of socio-political injustice that Manipur has historically gone through. The articulation of theatrical communication in his plays occurs happens more through silence, gestures, and sounds than through conventional verbal communications. He was creating in Manipur what his contemporary Pinter was creating in England, much at the same time, much in the same line, much with the same motif although with much difference in their context and artistic execution.